KINERJA KARYAWAN DI SEKOLAH MENENGAH PERTAMA: APAKAH DIPENGARUHI OLEH THE BIG FIVE PERSONALITY, PRODUKTIVITAS KARYAWAN, DAN WORK ENGAGEMENT? [EMPLOYEE PERFORMANCE IN JUNIOR HIGH SCHOOLS: IS IT INFLUENCED BY THE BIG FIVE PERSONALITY, EMPLOYEE PRODUCTIVITY, AND WORK ENGAGEMENT?] - Qodariah, Qodariah (Acta Islamica Counsenesia: Counselling Research and Applications, 2025)
In the current global era, an employee is required to be more professional in working. As is known, human resources are the part that supports and implements every process within the organization. Seeing SMP Negeri 32 Kota Tangerang which has a vision of "Pious, Achieving, and Environmentally Cultured" certainly requires resources that have good employee performance so that the vision can be realized. In addition, SMP Negeri 32 Kota Tangerang is also an inclusive and Adiwiyata school that must continue to be fought for in the future through the presence of teachers and educational staff at SMP Negeri 32 Kota Tangerang. The purpose of this study is to analyze: (a) the influence of the big five personality traits on employee performance at SMP Negeri 32 Kota Tangerang; (b) the influence of employee productivity on employee performance at SMP Negeri 32 Kota Tangerang; and (c) the influence of work engagement on employee performance at SMP Negeri 32 Kota Tangerang. This study uses a quantitative approach and is processed using SmartPLS software. The findings of this study are: (a) the big five personality traits do not have a significant effect on employee performance in Junior High Schools; (b) employee productivity has a significant effect on employee performance in junior high schools; and (c) work engagement has a significant effect on employee performance in junior high schools.